THE METROPOLISATION OF TIMIŞOARA, ROMANIA. AN EVALUATION BY URBAN FUTURE METHODOLOGY (PANGEEA, 2025)
Timişoara is one of the biggest five cities from Romania, an important Growing Pole in DKMT Euro-region. Timişoara is also very close by the Western National borders, close by four European capital, Bucharest, Belgrade, Budapest, and Wien that are less than 600 km away. After the political, social and economic changes after 1989 the city of Timişoara has to readapt to the new reality and challenges. As an inner-periphery, Timişoara has a limited development pattern, but the suburbanization could be the most efficient answer. This paper present the applying of the Urban Futures Methodology for evaluating the urban public policy in various scenarios of further evolution of the city. This work was supported by a grant of the Romanian National Authority for Scientific Research and Innovation, CCCDI-UEFISCDI, project number 66/2017 COFUND-ENSUF-3S RECIPE (1), within PNCDI III.
Keywords: Suburbanization; Urban Resilience; Inner Periphery; Urban Governance